A comparative study of the school environment of two technical schools implication for educational administration in Thailand - Ruksasub, Supoj 1943- (1974)
This survey looked into the characteristics of the school environment in 1973-1974 of the high school departments of two state-supported technical institutions, Marikina School of Arts and Trades and the Bulacan College of Arts and Trades as perceived by 209 students and 138 teachers of the two institutions. The students perceived the following characteristics in their schools: humanism, autonomy, equity to be often practiced while involvement, resources and morale were scored only sometimes. The faculty perceived the schools to be often humanistic. Involvement, autonomy, equity, resources, morale were perceived by them to be only sometimes evident. Student and faculty perceptions were highly correlated.
Thesis (M.Ed.)--University of the Philippines
Keywords: Bulacan College of Arts and Trade; Marikina School of Arts and Trade; School management and organization